Technical Assistance on Plant Cultivation Landslide Prevention in the River Flow Area in Kampung Bendang Nagari River Sariak VII Koto Padang Pariaman District - Suryani, Ade Irma suryani; Yuherman, Yuherman; Siregar, Lamina (PT FORMOSA CENDEKIA GLOBAL, 2024)
Watershed areas (watersheds are divided into upstream, middle and downstream areas. Upstream watersheds are characterized as conservation areas, have a higher drainage density and are areas with slopes of more than 15%, lower watersheds are characterized by areas with small slopes (less than 8% ) to flat, in some places it is a flood or puddle area. Water management is determined by irrigation water structures. The middle watershed is a transition area between upstream and downstream. (Asdak, 1995). main, (1) vegetative method, (2) Mechanical method, (3) Chemical method (Arsyad, 2010). In watershed spatial planning, vegetative methods and mechanical methods are recommended There are several methods that can be used to prevent landslides in watershed areas, both upstream, middle and downstream, but what is highly recommended is the Vegetative method and cultivating these plants